The sociology of aging a social problems perspective - Matcha, Duane A. (Allyn and Bacon, 1997)
Examines the aging process from a sociological perspective rather than a multidisciplinary one. Utilizing a social problems approach, this book examines how aging is a social construct, rather than a specific chronological age or set of conditions, and how aging is a consequence of various social structural factors, rather than a cause.